2014
DOI: 10.1097/htr.0b013e3182a61983
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Traumatic Brain Injury Rehabilitation

Abstract: There are significant differences in functional outcomes of TBI patients across rehabilitation centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 36 publications
0
13
0
1
Order By: Relevance
“…Consequently, there is notable variability in outcome measures across different facilities. 22 Considering this, the criteria of no benefit limitations allowed us to include patients who were able to fully undertake a comprehensive program.…”
Section: Post-acute Rehabilitation Improved Functional Outcomementioning
confidence: 99%
“…Consequently, there is notable variability in outcome measures across different facilities. 22 Considering this, the criteria of no benefit limitations allowed us to include patients who were able to fully undertake a comprehensive program.…”
Section: Post-acute Rehabilitation Improved Functional Outcomementioning
confidence: 99%
“…This team includes trained specialists in occupational therapy (OT), physical therapy (PT), speech language pathology (SLP), psychology, and physical medicine and rehabilitation . Results of prior studies have shown that IR outcomes can be greatly influenced by patient characteristics, clinical features, and variation in rehabilitation facilities …”
Section: Introductionmentioning
confidence: 99%
“…Efforts to provide standard of care for patients with TBI have led to the development of practice guidelines for clinicians and care providers to optimize patient outcome. Some of these guidelines provide specific information on duration or amount of treatments and patient participation . However, most of them have been developed based on non‐Canadian data, while it is recognized that the process of care can be affected by a variety of health care practices in various jurisdictions.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a growing recognition that there is variability in application of evidence-based guidelines, demonstrating a need for a standard treatment approach [4]. For example, amongst TBI Model System (TBIMS) rehabilitation centers, which provide a state-of-the-art multidisciplinary system of rehabilitation care [5], significant differences in risk-adjusted functional outcomes of TBI patients have been observed [57]. In the Traumatic Brain Injury-Practice Based Evidence study, it was determined that variations in care among TBIMS centers are due to differences in hospital characteristics, patient characteristics, and the experience of the clinicians [68].…”
Section: Introductionmentioning
confidence: 99%
“…In the Traumatic Brain Injury-Practice Based Evidence study, it was determined that variations in care among TBIMS centers are due to differences in hospital characteristics, patient characteristics, and the experience of the clinicians [68]. Differential patient outcomes across inpatient TBIMS centers may also relate to processes of care (e.g., goal and treatment planning, selection of therapeutic interventions) [5, 6, 9]. These variations in care may result from suboptimal adoption of evidence-based best practices in routine clinical care, with a little over half of adult patients in the U.S. receiving recommended preventative, acute, and chronic disease care [10, 11].…”
Section: Introductionmentioning
confidence: 99%